A comparative analysis of the antioxidant potential of watermelon (citrullus lanatus (thunb.)) mesocarp extract fractions evaluated by the DPPH method - Kusuma Ikhwan Yuda; Yunas Afrah; Febrina Dina; Csupor Dezső; Perdana Muhammad Iqbal; Pratiwi Hening (BIO Web of Conferences)
Watermelon mesocarp contains bioactive compounds with antioxidant properties that hold significant scientific and industrial interest. Antioxidants from natural sources are increasingly explored for applications in food preservation, cosmetics, and pharmaceuticals due to their efficacy and safety. This study aimed to identify fractions with strong antioxidant potential and explore their industrial applications. The crude extract was fractionated into water, ethyl acetate, and n-hexane fractions, and their antioxidant activity was evaluated using the DPPH method. The ethyl acetate fraction exhibited the strongest antioxidant activity, with an IC50 value of 7.68 ppm, which, while slightly less potent than ascorbic acid (IC50 = 4.09 ppm), demonstrated substantial free radical scavenging ability. This was followed by the water fraction (IC50 = 34.9 ppm), with the n-hexane fraction showing moderate activity (IC50 = 52.07 ppm). The ethyl acetate fraction of watermelon mesocarp extract demonstrated the strongest antioxidant activity, highlighting its potential for applications in food preservation and developing cosmetic formulations as a natural antioxidant source.